A mechanistic study of the non-oxidative decarboxylation catalyzed by the radical S-adenosyl-l-methionine enzyme BlsE involved in blasticidin S biosynthesis. Issue 64 (3rd July 2017) - Liu, Lei; Ji, Xinjian; Li, Yongzhen; Ji, Wenjuan; Mo, Tianlu; Ding, Wei; Zhang, Qi
Abstract : BlsE-catalyzed non-oxidative decarboxylation is initiated by a hydrogen abstraction from a sugar carbon of the substrate cytosylglucuronic acid (CGA). Abstract : Decarboxylation is a fundamentally important reaction in biology and involves highly diverse mechanisms. Here we report a mechanistic study of the non-oxidative decarboxylation catalyzed by BlsE, a radical S -adenosyl-l -methionine (SAM) enzyme involved in blasticidin S biosynthesis. Through a series of biochemical analysis with isotopically labeled reagents, we show that the BlsE-catalyzed reaction is initiated by the 5′-deoxyadenosyl (dAdo) radical-mediated hydrogen abstraction from a sugar carbon of the substrate cytosylglucuronic acid (CGA), and does not involve a carboxyl radical as has been proposed for 4-hydroxyphenylacetate decarboxylase (HPAD). Our study reveals that BlsE represents a mechanistically new type of radical-based decarboxylase.